Paediatric food‐induced anaphylaxis hospital presentations in New Zealand. (8th September 2017) - Speakman, Sophie; Kool, Bridget; Sinclair, Jan; Fitzharris, Penny
Abstract : Aim: Globally, rates of paediatric food‐induced anaphylaxis (FIA) are increasing. Little data is available regarding the epidemiology of FIA among New Zealand (NZ) children. This study investigated the incidence of paediatric (0–14 years) FIA hospital presentations in NZ over a 10‐year period. Methods: Ministry of Health public hospital discharge data from 2006 to 2015 were analysed using FIA‐related International Classification of Diseases codes (T78.0 – anaphylactic shock due to adverse food reaction and T78.2 – anaphylactic shock unspecified and free text qualifier) to identify acute hospital presentations. Results: The overall annualised FIA hospital presentation rate was 16.2 per 100 000 children. Subgroup analysis indicated a significantly higher rate in males (19.1/100 000) than in females (13.1/100 000), and among children aged less than 2 years of age (50.5/100 000) compared with older children. Rates among Asian and Pacific children were higher than Māori and NZ European children. In 67.7% of cases, a single specific allergen was suggested by the information provided; among these cases, nuts (48%), specifically peanuts (26%), were the most commonly reported allergen, followed by cow's milk (21%). Time trend analysis showed a 2.8‐fold increase in the overall annualised rate for the 10‐year period. Conclusion: These findings are consistent with other international studies indicating increasing rates of FIA in children. These data will provide information for a review of NZ paediatric allergy services to ensure current international standards with regard to the equitable delivery of timely, appropriate and accessible care are being met. Reasons for differences by gender, age and ethnicity require further investigation.